Dimorphism and population size of the Mexican redrump tarantula, Brachypelma vagans (Araneae: Theraphosidae), in Southeast Mexico - Yann Hénaut (Revista Mexicana de Biodiversidad, 2015)
As a general rule, spiders exhibit sexual dimorphism and their populations may differ in size according to season duration and resource availability. However, few studies have focused on dimorphism in tarantulas. Mexican redrump tarantulas, Brachypelma vagans , listed in CITES, have an exceptionally wide distribution. Surprisingly, there are no studies on the possible relationship between the abundance of tarantulas per population and the geographical areas where they are present, or on how the distribution pattern of this spider may affect individual morphological characteristics. Furthermore, there are no studies on sexual dimorphism within the genus Brachypelma . The aim of the study is to determine the existence of sexual and geographical dimorphism in populations of B. vagans . It was observed that the abundance of spiders per population may vary according to the geographical areas where they were recorded. In six localities in southern Mexico, we recorded morphological data on adult tarantulas. Sexual dimorphism was clearly observed at the site that presented numerous spiders characterized by much smaller females. Since the results of this study demonstrate differences in tarantula number of individuals per locality in southern Mexico, they make an important contribution to the conservation of this species. All Rights Reserved © 2015 Universidad Nacional Autónoma de México, Instituto de Biología. This is an open access item distributed under the Creative Commons CC License BY-NC-ND 4.0.